MUSLIM-FRIENDLY RESTAURANTS: A CRITICAL REVIEW FROM A MUAMALAT PERSPECTIVE - Ismail, Muhammad Saiful Islam; Ismail, Syaimak; Omar, Ahmad Afiq Irshad; Aziz, Aemy; Che Sobry, Suheil; Hanafi, Ahmad Harith Ashrofie; Nor A’zam, Muhammad Khairul Zharif; Mohd Zukhi, Mohd Zhafri (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The rapid expansion of the global halal food industry has significantly increased the number of Muslim-friendly restaurants in both Muslim-majority and minority markets. Existing studies show that halal certification, Islamic service quality, and Muslim-friendly hospitality attributes consumer trust, satisfaction, and loyalty. However, most research conceptualizes Muslim-friendly restaurants primarily from marketing and consumer behaviour perspectives. As a result, halal compliance is often evaluated mainly through certification status and customer perception, rather than through a broader Islamic ethical framework. This study addresses this gap by examining Muslim-friendly restaurant practices through the lens of Islamic commercial jurisprudence (Muamalat). In particular, the study investigates how restaurant operations reflect key Muamalat principles, including justice (ʿadl), transparency (bayan), avoidance of deception (tadlis), avoidance of excessive uncertainty (gharar), and protection of wealth (ḥifẓ al-mal). This study employs a qualitative conceptual research design through library research past studies on Muslim friendly in aspect of hospitality, ethical branding, and supply chain. The analysis indicates that current halal governance mechanisms primarily emphasize technical compliance, such as ingredient permissibility and supply chain integrity, while broader ethical dimensions of commercial conduct receive limited attention. Consequently, this study proposes a Muamalat-based conceptual framework linking Islamic ethical principles to restaurant operational practices and consumer outcomes. The framework highlights how ethical governance practices including fair pricing, transparent menu disclosure, ethical staff management, and halal supply chain integrity can strengthen consumer trust, satisfaction, loyalty, and perceived halal integrity.